'Are you a Billy, or a Dan, or an old tin can?': street violence and relations between Catholics, Jews and Protestants in the Gorbals during the inter-war years. (February 2014) - TAYLOR, AVRAM
ABSTRACT: This article makes use of memoirs, autobiographies and oral interviews in order to consider the relations between the Catholic, Jewish and Protestant communities in the Gorbals. While there was considerable variation in individual experience, there were also particular occasions where inter-ethnic relations were all too predictable, almost following a 'calendar of conflict'. The article shows that, while there was a degree of anti-Semitism in the area, integration between the Jewish and non-Jewish residents of the district was facilitated by a number of factors. Ultimately, anti-Semitism was mediated through the sectarian rivalry, which was the dominant religious conflict in the city.